Effect of castor oil emulsion eyedrops on tear film composition and stability - Maïssa, Cécile; Guillon, Michel; Simmons, Peter; Vehige, Joseph (Contact lens & anterior eye, 2010)
Abstract Purpose An emulsion eyedrop containing castor oil has been shown to modify the tear film lipid layer and increase tear film stability. The primary objectives of this investigation were to measure the prevalence of castor oil in the tear fluid over time and quantify the effects on the lipid layer. A secondary objective was to quantify the initial effects on ocular symptomatology. Methods The investigation was an open label pilot study on 5 normal and 10 dry eye subjects. A single eyedrop (Castor oil emulsion, Allergan) was instilled in each eye; the tear film appearance and composition were monitored for 4 h via in vivo visualisation using the Tearscope™ and post in vivo tear samples analysis by HPLC. Results Combined results for both normal and dry eye subjects showed that castor oil was detected up to 4 h after a single eyedrop instillation and associated with an increase in the level of tear film lipid. The relative amount of various lipid families was also changed. An increase in tear lipid layer thickness was significant up to one hour post-instillation for the symptomatic sub-population. The changes in tear film characteristics were associated with significantly lower symptoms up to four hours post-instillation for the symptomatic sub-population. Conclusion This pilot investigation showed that castor oil eyedrops achieved a residence time of at least four hours post-instillation, producing a more stable tear film and an associated significant decrease in ocular symptoms over the entire follow-up period for the symptomatic subjects.